2014
DOI: 10.1097/01.ehx.0000452614.96818.85
|View full text |Cite
|
Sign up to set email alerts
|

Histological study on the effect of vitamin C on ischemia–reperfusion injury in the adult rat ovary

Abstract: BackgroundOvarian torsion may cause serious complications such as infertility in young women. Conservative management includes detorsion and reperfusion of the twisted segment. However, it may have local and systemic consequences due to production of large amounts of reactive oxygen species during reperfusion of ovaries. Aim of workThe present work aimed to study the possible histological and immunohistochemical changes due to ischemia-reperfusion injury in rat ovaries and the possible protective effect of vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…From these results, it was concluded that the reperfusion after ischemia had done serious damage to the tissue and its cells. A previous study determined that p53 immunoreactivity in control group ovaries tissue was hardly observed but it was observed in the ischemia group (25). We found that p53 immunoreactivity did not show a statistical difference between groups.…”
Section: Discussioncontrasting
confidence: 48%
“…From these results, it was concluded that the reperfusion after ischemia had done serious damage to the tissue and its cells. A previous study determined that p53 immunoreactivity in control group ovaries tissue was hardly observed but it was observed in the ischemia group (25). We found that p53 immunoreactivity did not show a statistical difference between groups.…”
Section: Discussioncontrasting
confidence: 48%
“…It protects body tissues against oxidative damage. Nasr et al (2014) showed the ameliorating effect of vit C after ischemia-reperfusion in adult rat ovary. Abbasi et al (2016) investigated the effect of vit C on monosodium glutamate inducing changes in the rats ovary.…”
Section: Discussionmentioning
confidence: 97%
“…Vitamin C is a safe and easy drug that can protect the ovaries from ischemia-reperfusion damage caused by detour, which is the main conservative method for managing ovarian torsion (61). Sagsoz et al, who studied the effects of antioxidants on the ovaries, reported that vitamin C reduced ischemia-reperfusion of the ovaries in its early stages, which is better than verapamil, a calcium channel blocker (75).…”
Section: Ovary Testicularmentioning
confidence: 99%